Pencapaian Triple Bottom Line pada Berdaya Charity Store sebagai Upaya Sociopreneurship - Yusuf, Raidah Intizar; Ernawati, Ernawati (Jurnal Penelitian Kesejahteraan Sosial, 2019)
This research departs from the rising phenomenon of philanthropic activities that have social-based humanitarian objectives based on fundraising and the presence of sociopreneurship namely entrepreneurial activities that emphasize social impact as a solution for philanthropic organizations to maintain the sustainability of fundraising. Berdaya Charity Store is unique because of its emphasis on Triple Bottom Line, i.e. financial, social, and environmental. This paper aims to explore the Triple Bottom Line at Berdaya Charity Store, so that we can formulate useful suggestions for the store in particular, also to other sociopreneurship who have aspirations to become professional philanthropists with social impact objectives. This research was conducted with a qualitative approach, the method used was participatory observation, interviews, documentation and library research. Throughout the researcher's observations, efforts to achieve the lines have been carried out well. The store invites people to donate used goods to be sold in stores, and most of the funds are used for social activities in the form of visits to orphanages and training in hard and soft skills. But we also observed that although the social mission was integrated with the revenue model, the overall and diversity of income from the store was still low, i.e. donations and sales. Therefore it becomes natural when most of the funds are used for social activities.